Mechanical Properties and Durability of High-Performance Concretes Blended with Circulating Fluidized Bed Combustion Ash and Slag as Replacement for Ordinary Portland Cement - Zhi Cheng; Lei He; Lan Liu; Zhijun Cheng; Xiaobo Pei; Zhe Ma (Advances in Materials Science and Engineering)
This study investigates the mechanical properties and durability of three families of high-performance concrete (HPC), in which the first was blended with fly ash, the second with circulating fluidized bed combustion (CFBC) ash, and the third with CFBC slag. In addition to each of the three mineral additives, silica fume and a superplasticizer were also incorporated into the HPC. Hence, three families of HPC, containing 10%, 20%, and 30% mineral admixtures and 9% silica fume of the binder mass, respectively, were produced. The microstructure and hydration products of the HPC families were examined by scanning electron microscopy (SEM) and X-ray diffraction (XRD) to explore the influence of fly ash, CFBC ash, and CFBC slag on the compressive strength and frost resistance of HPC. The experimental results show that the compressive strength of HPC could reach 60 MPa at 28 d age. When the fly ash content was 30%, the compressive strength of HPC was 70.2 MPa at 28 d age; after the freeze-thaw cycle, the mass loss and strength loss of HPC were 0.63% and 8.9%, respectively. When the CFBC ash content was 20%, the compressive strength of HPC was 75 MPa at 28 d age. After the freeze-thaw cycle, the mass loss and strength loss of HPC were 0.17% and 0.81%, respectively.